Spillover Effects in Mutual Fund Companies - Sialm, Clemens; Tham, T. Mandy (Management Science, 2016)
Our paper investigates spillover effects across different business segments of publicly traded financial conglomerates. We find that the investment decisions of mutual fund shareholders do not depend only on the prior performance of the mutual funds; they also depend on the prior performance of the funds’ management companies. Flows into equity and bond mutual funds increase with the prior stock price performance of the funds’ management companies after controlling for fund performance and other fund characteristics. The sensitivity of flows to the management company’s performance is not justified by the subsequent performance of the affiliated funds. The results indicate that the reputation of a company’s brand has a significant impact on the behavior of its customers. This paper was accepted by Wei Jiang, finance.